ANALISIS PENGENDALIAN JUMLAH CRUDE OIL SEBELUM DAN SESUDAH PANDEMI COVID-19 DENGAN PENDEKATAN ECONOMIC ORDER QUANTITY - Fitriani Surayya Lubis; Afif Naufal Luthfi; Laila Surayya (Jurusan Teknik Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2022)
Inventory control is a main activity for managing the amount of raw material inventory of the industry production process. PT. Pertamina RU II Dumai which engaged in oil and gas business activities have used Crude Oil as the major raw material in the fuel production process. Based on preliminary observation, it was found that the demand for avtur fuel was unstable during the period 2019-2020, decreasing to 54% whereas diesel fuel increasing to 17%. Consequently, this has an impact on the number of Crude Oil orders and also the inventory management. This study aims to determine the optimal amount of inventory, safety stock, the reorder point, and the ratio analysis of the amount raw material used during the era before and after pandemic covid-19 situation 2019 to 2020. Economic Order Quantity (EOQ) approach is proposed to place orders in the amounts that best fit its needs. The results of this study indicate that the number of purchases of raw materials using the EOQ method in 2019 and 2020 amounted to 3,525,563,777 BBL and 2,427,392.443 BBL. Total safety stock in 2019 was 10,031,979.39 BBL, while in 2020 it was 8,733,637.21 BBL. The number of reorder points in 2019 was 3,035,881,925 BBL and in 2020 it was 2,321,768,481 BBL. Regarding to this economic purchase of raw material quantity, it is found that the order size of Crude Oil decreased around 31.1% after the pandemic hit.